Innovative Porcelain Insulators: Prolonged Durability and Anti-Contamination Efficiency via Nano-TiO2 Photocatalyst Integration - Bangshidhar Goswami (International Journal of Crystalline Materials, 2024)
Porcelain has long been a critical material in high-voltage electrical insulation due to its exceptional mechanical, thermal, and dielectric properties. However, environmental contamination and material degradation over time pose significant challenges to its durability. This study investigates the integration of nano-sized titanium dioxide (TiO2) photocatalyst coatings on porcelain insulators to enhance their performance and prolong their operational lifespan. Local clay compositions were analyzed, and a comparative study of untreated and TiO2-treated porcelain samples was conducted using Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD) to evaluate structural, chemical, and surface modifications. Results demonstrated that TiO2 coatings significantly improved contamination resistance by enabling self-cleaning under environmental exposure, leading to enhanced electrical insulation performance. Furthermore, mechanical and thermal tests showed that the addition of TiO2 did not compromise the inherent properties of porcelain, but instead contributed to a reduced degradation rate under prolonged service. These findings suggest that nano-TiO2 coatings offer a viable solution for extending the operational life of porcelain-based insulators in harsh environments. The study also highlights the potential for incorporating nano-technological advancements in traditional ceramic materials, opening avenues for more sustainable and cost-effective solutions in high-voltage insulation systems. The adjustable qualities of porcelain have prompted research on this topic. Assess has exposed in-service correspondence to fresh research. Value engineering aspects have been confirmed through feature-specific evaluations of local clay features. With the addition of a coat of nano-sized titanium dioxide (TiO2) photocatalyst, nano-contamination technology for outdoor high-voltage ceramic insulators has improved the performance of the ceramic insulators under contaminated conditions.
Keywords: Electrical Insulation; Porcelain; environmental durability; insulators nano-TiO2 coating; photocatalysis